Performance of masonry enclosure walls: lessons learned from recent earthquakes - Vicente, R. (2012)
This paper discusses the issue of performance requirements and construction criteria for masonry enclosure and infi ll walls. Vertical building enclosures in European countries are very often constituted by non-load-bearing masonry walls, using horizontally perforated clay bricks. These walls are generally supported and confi ned by a reinforced concrete frame structure of columns and beams/slabs. Since these walls are commonly considered to be nonstructural elements and their infl uence on the structural response is ignored, their consideration in the design of structures as well as their connection to the adjacent structural elements is frequently negligent or insuffi ciently detailed. As a consequence, nonstructural elements, as for wall enclosures, are relatively sensitive to drift and acceleration demands when buildings are subjected to seismic actions. Many international standards and technical documents stress the need for design acceptability criteria for nonstructural elements, however they do not specifi cally indicate how to prevent collapse and severe cracking, and how to enhance the overall stability in the case of moderate to high seismic loading. Furthermore, a review of appropriate measures to improve enclosure wall performance and both in-plane and out-of-plane integrity under seismic actions is addressed.